2017
DOI: 10.1534/genetics.116.195297
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of WNT Signaling at the Neuromuscular Junction by the Immunoglobulin Superfamily Protein RIG-3 inCaenorhabditis elegans

Abstract: Perturbations in synaptic function could affect the normal behavior of an animal, making it important to understand the regulatory mechanisms of synaptic signaling. Previous work has shown that in Caenorhabditis elegans an immunoglobulin superfamily protein, RIG-3, functions in presynaptic neurons to maintain normal acetylcholine receptor levels at the neuromuscular junction (NMJ). In this study, we elucidate the molecular and functional mechanism of RIG-3. We demonstrate by genetic and BiFC (Bi-molecular Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
(132 reference statements)
1
16
1
Order By: Relevance
“…RIG-3 is expressed in AVA command interneurons and a small number of pharyngeal interneurons as well as in cholinergic motor neurons (Schwarz et al 2009;Babu et al 2011). Previous studies have also shown that RIG-3 functions at the neuromuscular junction, where it has been reported to regulate the acetylcholine receptor delivery (Babu et al 2011;Pandey et al 2017). Our results suggest that animals lacking rig-3 show more frequent spontaneous reversals in comparison to WT control animals ( Figure 1).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…RIG-3 is expressed in AVA command interneurons and a small number of pharyngeal interneurons as well as in cholinergic motor neurons (Schwarz et al 2009;Babu et al 2011). Previous studies have also shown that RIG-3 functions at the neuromuscular junction, where it has been reported to regulate the acetylcholine receptor delivery (Babu et al 2011;Pandey et al 2017). Our results suggest that animals lacking rig-3 show more frequent spontaneous reversals in comparison to WT control animals ( Figure 1).…”
Section: Discussionsupporting
confidence: 74%
“…Studies have shown that RIG-3 plays an important role in maintaining acetylcholine receptor levels at the neuromuscular junction (Babu et al 2011;Pandey et al 2017). Apart from showing expression in cholinergic motor neurons, RIG-3 also shows expression in the anterior region that is thought to be restricted to the command interneuron AVA and pharyngeal neurons (Schwarz et al 2009).…”
Section: Mutants In Rig-3 Show Increased Reversalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study shows that ACR‐16/α7 receptor translocation is mediated by members of the canonical Wnt signaling pathway . Out of five Wnts LIN‐44, EGL‐20, CWN‐1, CWN‐2 and MOM‐2 in C. elegans , CWN‐2 and LIN‐44 are involved in this pathway. The Wnts, CWN‐2 and LIN‐44 secreted from the presynaptic neurons, bind and activate the postsynaptic Wnt receptor Lin‐17/Frizzled.…”
Section: Hic‐1 and The Regulation Of Acr‐16/α7 Receptor Traffickingmentioning
confidence: 99%
“…Most of the excitatory currents at the C. elegans NMJs are mediated by nicotine‐sensitive ACR‐16/α7 (nAChR) receptors. The surface expression of these receptors is regulated through the Wnt signaling pathway . Jensen et al have elegantly dissected out the Wnt signaling pathway, which regulates the translocation of ACR‐16/α7 receptors at the C. elegans NMJs.…”
Section: Hic‐1 and The Regulation Of Acr‐16/α7 Receptor Traffickingmentioning
confidence: 99%